UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN AKHLAK DAN KETAATAN IBADAH SISWA DI SDN 1 WONOSARI: indonesia - Hidayatun Soleha; Ulfa Umurohmi; Salamun (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Abstract The problem in this research is how the efforts of PAI teachers in improving students' morality and obedience of worship so that students can have noble character both in personal life, in society, nation and state. In addition, to improve the faith, understanding, appreciation and practice of students about Islam. This study aims to determine the morals and obedience of worship of students in schools, efforts or methods of PAI teachers in improving the morality and obedience of worship of students, Knowing the obstacles or obstacles perceived by PAI teachers, and knowing the results of PAI teachers 'efforts in improving students' morals and obedience SDN 1 Wonosari. The method used by PAI teachers in improving students' morality and obedience in worship is using habituation methods, exemplary methods, and giving reward and punishment. This research is a qualitative research. The population of this study were all students of SDN 1 Wonosari class I-VI which amounted to 154 students and the samples were class VI students, amounting to 29 children. The technique of collecting data uses library studies, interviews, documentation, and observation. Data are analyzed using techniques including data reduction, data presentation, and conclusion drawing. The results of this study indicate that the habituation method, exemplary method, and reward and punishment make students more disciplined, moral, and more motivated in doing good and more careful in acting. Keywords: Teacher, Morals, Worship Abstrak Permasalahan dalam penelitian ini adalah bagaimana upaya guru PAI dalam meningkatkan akhlak dan ketaatan ibadah siswa agar peserta didik dapat berakhlak yang mulia baik dalam kehidupan pribadi, bermasyarakat, berbangsa dan bernegara. Selain itu, untuk meningkatkan keimanan, pemahaman, penghayatan dan pengamalan peserta didik tentang agama islam. Penelitian ini bertujuan untuk mengetahui akhlak dan ketaatan ibadah siswa di sekolah, upaya atau metode guru PAI dalam meningkatkan akhlak dan ketaatan ibadah siswa, Mengetahui kendala atau hambatan yang dirasakan guru PAI, serta mengetahui hasil dari upaya guru PAI dalam meningkatkan akhlak dan ketaatan ibadah siswa di SDN 1 Wonosari. Metode yang digunakan oleh guru PAI dalam meningkatkan akhlak dan ketaatan ibadah siswa yaitu menggunakan metode pembiasaan, metode keteladanan, dan pemberian reward dan punishment. Penelitian ini merupakan penelitian kualitatif. Populasi dari penelitian ini adalah semua peserta didik SDN 1 Wonosari kelas I-VI yang berjumlah 154 siswa dan sampelnya yaitu peserta didik kelas VI yang berjumlah 29 anak. Teknik pengumpulan data menggunakan studi perpustakan, wawancara, dokumentasi, dan observasi. Data dianalisis menggunakn teknik-teknik diantaranya reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan bahwa dengan metode pembiasaan, metode keteladanan, dan pemberian reward dan punishment membuat siswa menjadi lebih disiplin, berakhlakul karimah, dan lebih termotivasi lagi dalam berbuat kebaikan serta lebih berhati-hati dalam bertindak. Kata Kunci :Guru, Akhlak, Ibadah